Exploring the Gokak language movement in Karnataka, one of India’s richest states: the Kannada sub-nationalism project - Sreeram Gopalkrishnan (Cogent Arts & Humanities)
The 2023 state elections in Karnataka, one of the richest states in India, with the IT hub Bengaluru as its capital, threw up an issue of state sovereignty in the campaign crossfire between the country’s two leading political parties - the right wing Bharatiya Janata Party and centre-left Indian National Congress. The incident brought back memories of the Kannada sub-nationalism project in the 1980s which came to be known as the Gokak movement. That crusade for Kannada primacy may have been the best opportunity for language activists to replicate, in Karnataka, the electoral success of the Dravida Munnetra Kazhagam’s1 sub-nationalism political project on Tamil exceptionalism in the neighbouring state, Tamilnadu. The diverse linguistic space of the region, the legacy of the Mysore princely state and the persona of Kannada cinema superstar Dr Rajkumar (who supported the movement at first and did not follow through with a political role), may all have played an important part in the fate of the Kannada language movement. The INC won the electoral contest but we may see the re-emergence of old faultlines and in the atmosphere of majoritarian nationalism of centralisation in a federal set-up and the beginnings of a new frontline of cultural wars in India.